Analysis and monitoring of roadway deformation mechanisms in nickel mine, China. (10th October 2018) - Lu, Rong; Ma, Fengshan; Guo, Jie; Zhao, Haijun
Summary: Deformation of surrounding rock of roadway in deep is an important issue for mining engineering. We did some investigations and monitoring works in Jinchuan Mine 2. In this paper, based on field investigation, roadway deformation was summarized three features: horizontal displacement of roadway is larger than vertical displacement; roadway deformation has time effect, and also has large convergence. The monitoring data showed that roadway deformation was influenced by mining operation, but the scope of mining influence is not large. Roof conditions have effect to deformed process of roadway. Three mechanisms of surrounding rock deformation were analyzed that are rock dilatancy mechanism; shearing wedges block slide mechanism; springback of surrounding rock mechanism. We compared these mechanisms to field rock failure.